Hardcore drug addict treatment method through spiritual approach: a case study in Pondok Remaja Inabah 1 Malaysia, Kedah - Abd Ghani, Abdullah; Maamor, Selamah; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Abd. Wahab, Norazlina; Nik Abdullah, Nik Safiah; Elias, Nor Hanim (Akademia Baru, 2017)
This article explain method carried out by Pondok Remaja Inabah (1) Malaysia (PRI(1)M) for rehabilitation of drug addict, teenage social issues, as well as those who suffer from unpeaceful mind to return to the right path according to God's command.This case study was carried out by conducting multiple interviews and observations with PRI(1)M management team at their place. Each of the PRI(1)M’s participant (anak bina) will undergo three treatment methods, namely bath of repentance, prayer and remembrance (zikr). This method emphasizes the concept of recovery as well as the spiritual and physical guidance. Up to now PRI(1)M has treated more than 7000 of drug addicts (participants) and about 70% had been restored by the permission of God. Although PRI(1)M are faced with financial difficulties, PRI(1)M still capable to build the respected participants after they undergoing a rehabilitation program through spirituality approach. Among the key factors of this successful that can be identified is a strict censorship before admission; donations and services provided by the participants who have successfully rehabilitated and rejoin PRI(1)M togather help other participants with the spirituality approach; determination and sincerity of the founder and also the PRI(1)M’s management team. The results of this case study found that a spiritual approach by PRI(1)M capable and proven successful to recover hardcore drug addicts. Thus, the success of PRI(1)M can be used as a model for hardcore drug addicts recovery.